Structural Transformations and Magnetic Properties of Mixed Spinel‐Type NiCr1.7Fe0.3O4 Nanoparticles. Issue 11 (12th September 2021) - Pandey, Gaurav Chandra; Su, Yixi; Rath, Chandana
Abstract : Structural and magnetic properties of NiCr1.7 Fe0.3 O4 nanoparticles, synthesized by a facile coprecipitation method, are examined using temperature‐dependent X‐ray diffraction, neutron scattering with XYZ polarizations, and magnetic measurements. The structural analysis demonstrates the stabilization of the cubic phase down to 200 K, followed by a low‐temperature tetragonal phase at 100 K and an orthorhombic phase below 50 K. The refined occupancies of cations demonstrate that the NiCr1.7 Fe0.3 O4 is a mixed spinel compound, wherein B sites are populated by ≈85% Cr 3+ and ≈15% Ni 2+ cations and A sites are populated by ≈70% Ni 2+ and ≈30% Fe 3+ cations. As a consequence, the reduction in the occupancy of Jahn–Teller active Ni 2+ (triply degenerate: e 4   t 4 ) at A site is attributed to the stabilization of the cubic phase below room temperature. Temperature‐dependent magnetization and neutron scattering with XYZ polarizations measurements reveal the ferrimagnetic nature of the magnetic phase and the absence of spin‐spiral ordering in NiCr1.7 Fe0.3 O4 nanoparticles. Furthermore, field‐dependent magnetization measurement demonstrates an exchange bias field of ≈134.5 kA m −1 at 5 K. The training effect measurement is performed to discuss the origin of exchange bias based on different phenomenological models such as power‐law and multiexponent models. Abstract : Mixed spinel‐type NiCr1.7 Fe0.3 O4 nanoparticles demonstrate a rich sequence of structural and magnetic phase transitions below room temperature. They show cubic‐‐tetragonal‐‐orthorhombic phase transitions and para to ferrimagnetic phase transitions. In addition, NiCr1.7 Fe0.3 O4 exhibits an exchange bias field of ≈134.5 kA m −1 which can make it a potential candidate for spin valves, read heads, and magnetic tunnel junction‐based devices.